IMPROVING ANECDOTE TEXT WRITING SKILLS USING GOOGLE CLASSROOM MEDIA FOR CLASS X STUDENTS TKI 2 VOCATIONAL SCHOOL NEGERI 5 SURABAYA - Dina Wahyu K; Rini Damayanti; Sumara Arisanthi (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
The aim of the research is to determine the improvement in writing skills of class X TKI 2 SMK Negeri 5 Surabaya after the implementation of the Google Classroom learning media?Writing is a skill that does not just appear suddenly, but develops through a gradual process. This process starts with a basic understanding of language and written structure, which then develops through continuous practice. Every stage in the writing process, from stringing words together to forming paragraphs and organizing ideas coherently, takes time and dedication. As time goes by, a person's writing ability will improve, reflecting maturity of thinking and greater clarity of expression. Every new piece of writing is an opportunity to learn and develop further. Even experienced writers continue to learn and improve their skills with each new work they produce. This process allows writers to continually explore new ideas, try different writing styles, and overcome new challenges in expressing themselves. Anecdotal texts are often structured by presenting situations or events that make the characters feel annoyed or ridiculous. These situations usually describe moments where a person's hopes or expectations conflict with the reality at hand, thereby triggering mixed emotional reactions. The sense of ridiculousness in anecdotal texts not only serves as entertainment, but as the main driving force of the story. Classroom Action Research (PTK) is a research method carried out by teachers in their own classes with the aim of improving the efficiency and quality of education. PTK focuses on observing and evaluating the ongoing learning process, as well as efforts to find and implement strategies that can improve student learning outcomes. Keywords: writing, anecdote text, classroom action research.